Effect of CpG dinucleotides within IgH switch region repeats on immunoglobulin class switch recombination. Issue 2 (August 2015) - Zhang, Zheng Z.; Hsieh, Chih-Lin; Okitsu, Cindy Yen; Han, Li; Yu, Kefei; Lieber, Michael R.
Highlights: The CpG motif is rare within mammalian IgH class switch recombination repeats. Two CpG sites per 80 bp synthetic Sα switch repeat induces methylation at the Iα, resulting in lower transcription. CpG sites within the repetitive Sα region trigger DNA methylation around the promoter. Ig switch repeats evolved to have few CpG sites to avoid suppression of the promoter. Abstract: Immunoglobulin (Ig) heavy chains undergo class switch recombination (CSR) to change the heavy chain isotype from IgM to IgG, A or E. The switch regions are several kilobases long, repetitive, and G-rich on the nontemplate strand. They are also relatively depleted of CpG (also called CG) sites for unknown reasons. Here we use synthetic switch regions at the IgH switch alpha (Sα) locus to test the effect of CpG sites and to try to understand why the IgH switch sequences evolved to be relatively depleted of CpG. We find that even just two CpG sites within an 80 bp synthetic switch repeat iterated 15 times (total switch region length of 1200 bp containing 30 CpG sites) are sufficient to dramatically reduce both Ig CSR and transcription through the switch region from the upstream Iα sterile transcript promoter, which is the promoter that directs transcripts through the Sα region. De novo DNA methylation occurs at the four CpG sites in and around the Iα promoter when each 80 bp Iα switch repeat contains the two CpG sites. Thus, a relatively low density of CpG sites within the switch repeats can induce upstream CpG methylation at the IgH alpha locus, and cause a substantial decrease in transcription from the sterile transcript promoter. This effect is likely the reason that switch regions evolved to contain very few CpG sites. We discuss these findings as they relate to DNA methylation and to Ig CSR.